Transcriptome-wide 1-methyladenosine functional profiling of messenger RNA and long non-coding RNA in bladder cancer - Yin, Jian-jian; Song, Yan-liang; Guo, Yu-feng; Dai, Yuan-heng; Chang, Qi; Wang, Tao; Sun, Guo-qiang; Lu, Ping; Song, Dong-kui; Zhang, Li-rong (Frontiers in Genetics, 2024)
Post-transcriptional RNA modifications are crucial regulators of tumor development and progression. In many biological processes, N1-methyladenosine (m1A) plays a key role. However, little is known about the links between chemical modifications of messenger RNAs (mRNAs) and long noncoding RNAs (lncRNAs) and their function in bladder cancer (BLCA). Here, methylated RNA immunoprecipitation sequencing and RNA sequencing were performed to profile mRNA and lncRNA m1A methylation and expression in BLCA cells, with or without stable knockdown of the m1A methyltransferase tRNA methyltransferase 61A (TRMT61A). The analysis of differentially genes identified 16,941 peaks, 6,698 mRNAs, and 10,243 lncRNAs in the two groups. Gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analyses of the differentially methylated and expressed transcripts showed that m1A-regulated transcripts were mainly related to protein binding and signaling pathways in cancer. In addition, the differentially genes were identified that were also differentially m1A-modified and identified 14 mRNAs and 19 lncRNAs. Next, these mRNAs and lncRNAs were used to construct a lncRNA-microRNA-mRNA competing endogenous RNA network, which included 118 miRNAs, 15 lncRNAs, and 8 mRNAs. Finally, the m1A-modified transcripts, SCN2B and ENST00000536140, which are highly expressed in BLCA tissues, were associated with decreased overall patient survival. Taken together, this study revealed substantially different amounts and distributions of m1A in BLCA after TRMT61A knockdown and predicted cellular functions in which m1A may be involved, providing evidence that implicates m1A mRNA and lncRNA epitranscriptomic regulation in BLCA tumorigenesis and progression.